NATURAL DYE’S SAFE AND ECO-FRIENDLY - Rajbhar, Karishma; Dawda, Dr. Himanshu; Mukundan, Dr. (Mrs.) Usha (IJRDO-Journal of Applied Science, 2016)
Natural dyes present in plants pigments like betalaines, xanthophylls, anthocyanins, chlorophylls, tannins, flavonoids, etc can be used as natural colours for various industries like food, beverages, cosmetics, textiles etc. As manufacturing and disposal of the enormous effluents formed during synthetic dye are affecting environment. Natural dyes can be rescue to us if used in smart manner. Waste vegetables and others plant product damaged during transportation used as a source of natural dye. The results are incredible and are also safe for skin and do not cause any allergies. Natural dyes are also eco-friendly, thus helping us to save our nature.